Appendicitis in Children in a Large Italian COVID-19 Pandemic Area - La Pergola, Enrico; Sgrò, Alberto; Rebosio, Federico; Vavassori, Daniele; Fava, Giorgio; Codrich, Daniela; Montanaro, Beatrice; Leva, Ernesto; Schleef, Jurgen; Cheli, M.; Pelizzo, Gloria; Gamba, Piergiorgio; et al. (Frontiers in Pediatrics, 2020)
Introduction COVID-19 pandemic has dramatically changed the routinely activities of Paediatric surgical Centres and it determined the reduction of admissions in the Paediatric Emergency Departments (PED). We reviewed the records of patients affected by acute appendicitis (AA) during the COVID-19 pandemic period in a large Italian COVID-19 pandemic area. Methods Data regarding demographics, age, macroscopic and microscopic findings, and time between symptoms onset and PED admission of patients affected by confirmed AA in the period between March and April 2020 were considered. The data were compared with those obtained during the same period of 2019, 2018 and 2017 in the included Centres. Data were quoted as median (range) or absolute number. Non-parametric statistical tests were used to compare groups. A P value of ≤0.05 was regarded as significant. Since only anonymous data have been used and the data storage meets current data protection regulations the ethical committee approval was not required for this study. Results 86 patients underwent surgical appendectomy for AA between February 20th 2020 and April 20th 2020. 32.5% were complicated appendicitis and 67.5% were uncomplicated. 53 patients were males, 33 were females. Patients age ranged from 3 to 17 years and the median age was 10 years. The median time between the onset of symptoms and the admission in PED was 1.85 days. The average time between the symptoms onset and PED admission was 1.8 days. Conclusions Although the fear from COVID-19 pandemic determined a delayed diagnosis of serious paediatric diseases, the increasing of prevalence and severity of AA were not demonstrated in the COVID-19 most affected areas of Italy.